THE LOCAL ANTIOXIDANT INDEX – CRITERION FOR ASSESSING INTESTINAL COLONIZATION RESISTANCE AND THE RISK OF CHRONIC SYSTEMIC INFLAMMATION DEVELOPMENT WITH CHRONIC HEPATITIS C AFTER AUTOHAEMOTHERAPY - M. N. Gapon; L. N. Ternovskaya (Медицинский вестник Юга России, 2015)
Purpose: identifying patterns of changes in the general and local antioxidant index in the dynamics of experimental dysbiosis.Materials and methods: the model of the experimental dysbiosis was reproduced on 200 male mice, by means of intraperitoneal injection of gentamicin The control group consisted of 50 intact animals. In coprofiltrates and in the blood of mice, there was examined the activity of antioxidant enzymes (superoxide dismutase and catalase) and content of malondialdehyde. The biochemical parameters were assessed photometrically at an optical density value of the samples. The miicrobial landscape of feces was determined by classical bacteriological method. All figures were examined on the 3, 10, 17, 24, 30 day after the 5-day course of antibiotics.Results: it was found that by an increase in the total number of opportunistic microbes as part of the large intestine microbiocenosis, a reduction in general and local antioxidant index takes place, with a significant advantage of the latter.Conclusion: on the basis of the calculation of the local antioxidant index there was proposed screening criterion to evaluate the state of the colonization resistance of the large intestine with the establishment of the risk of chronic systemic inflammation development.